Serbest bölgeler ve serbest bölge bankacılığı - Odabaş, Kenan (My University, 2006)
Tezde Türkçe Özet yok. SUMMARY Free trade zones are considered as one of the most important tools for increasing the volume of exports especially by the countries who preferred export-oriented development strategy around the world and they were utilized in this way. To create the appropriate atmosphere for development, to select the sectors that will become important in the future and to promote these sectors, in other words by attracting foreign capital and technology to become an imporatant player in the world economy are among the main objectives of free trade zone implementation. If the free trade zones are considered as the gates to abroad, it is natural for Turkish Banking System to be presented at free trade zones. The main objective of the established banks in Turkey to open branches at free trade zones is to provide banking services to the companies presented at free trade zones. Besides, to open up new frontiers and to prepare international trade possibilities through the free trade zones for the banks active in Turkey are also among the objectives. In this study, the theoretical structure of the free trade zones, its history, exercises in Turkey and around the world, the banking implementations at free trade zones, the characteristics of the free trade zone banking, off-shore banking and the development of our free trade zones in the European Union adaptation process are explained. The philosophy of free trade zone in Turkey should be to strengthen our position around the world by utilizing our commercial and industrial potential fully in spite of finding magical solutions to economical problems by new free trade zone announcements.
Keywords: Bankalar ve Bankacılık_Muhasebe; Serbest Bölgeler_Bankalar ve Bankacılık